“I Can’t Really Work Any ‘Normal’ Job:” Disability, Sexual Ableism, and Sex Work - Jones, Angela (Disability Studies Quarterly, 2022)
Scholars studying sex work are often guided by compulsory able-bodiedness, asking sex workers for demographic information such as race, gender, and socio-economic position but not about disabilities. In addressing sexual ableism and the reproduction of compulsory able-bodiedness in studies of sex work, I demonstrate how disability is both a factor determining sex work participation and how sex work is a vehicle for disabled workers to explore their sexuality and disrupt tired stereotypes regarding disability and sexuality. In this article, I draw from data from two different studies 1) a five-year mixed-methods study on the erotic webcam industry and 2) an interview-based study on the workplace experiences of transmasculine and non-binary escorts. I use these data to demonstrate the role of disability, especially chronic illness, in individual motivations for entry into sex work. Research on sex work generally relies upon and proffers economically deterministic theories that show how whether, by choice or circumstance, people look to sex work for the same reasons they look for any job in a capitalist system—wages. However, the use of an intersectional frame yields richer results. Here, I also explore the convergence of cissexism and ableism in the lives of disabled trans sex workers, demonstrating how, for the most marginal, sex work is often a lifeline. Further, I examine the implications of these findings for thinking about disability justice movements and pushing back on capitalist, white supremacist, and ableist notions of productivity that have come to govern our lives.